EFFECT OF USING TREATED WATER WITH POTASSIUM PERMAGANATE AND CHLORINE ON SOME HEAMATOLOGICAL TRAITS IN LOCAL FEMALE RABBITS - D. H. Y. Al-Zwean,; Z. K. Ibrahim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to find out the effect of using treated water with potassium permanganate and chlorine on some hygienic traits of local female rabbits. This experiment was carried out in Farm Animal of veterinary College – Baghdad university lasted from 7th January up to 6th April 2016. Twenty eight local female rabbits at age of approximately 2.5-3 months and divided randomly and equally (7 each) into four groups 'body weight was considered" as the following: First group (boiling water group) considered as a (Negative control), second (Tap water group) as a positive control, Third(KMnO4 0.5 ppm), fourth (KMnO4) 1ppm) group. All groups were daily fed on concentrate diet (75 gm/head), all groups were offered alfalfa and specific water each group freely. Blood samples were taken and blood serum samples were obtained to find out the hemoglobin concentration (Hb), packed cell volume (PCV), Total protein and its fraction (Albumin and globulin). Data were statically analyzed, and the results of this study were revealed the existence of significant and non-significant differences to some hygienic traits between group of different periods. Accordingly, it could be concluded from this study, the disinfection effectivity of chlorine and potassium permanganate in water could be contribute to improving some hygienic traits of locally reared rabbits, also the disinfection efefctivity of chlorine in waster exceeded the disinfection effectivity of potassium permanganate through the used of water in improving the hygienic traits of rabbits due to the fact that water quality had direct impact on the health performance of the animal.